Training and information literacy of Brazilian medical librarian - Azevedo, Alexander Willian (2010)
This study aimed to investigate the different approaches on the training of medical librarians, in order to observe their characteristics and proposals, and to identify the information literacy that would be desirable to these professionals in Brazil. Whereas the practice of the Medical Librarianship is recent in Brazil, the method used to achieve the proposed objectives has been developed through literature review of texts extracted from national and international databases It also took advantage of its qualitative character, due to the fact of being bibliographical research of self exploratory nature, which made possible to observe the main skills and information literacy of medical librarians. The main results of the research indicate that librarianship schools in Brazil went through several reformulations in their curricula, to enable librarians to take initiatives, have motivation, proactive attitudes and to be receptive to changes, in order to act in several areas of knowledge, including medical field. The results also demonstrated that the main characteristics of Brazilian medical librarians do not differ from the general profile of librarians, meaning that they should not have special skills to work in specialized libraries.